Efficacy of multiple microwave endometrial ablation technique for menorrhagia resulting from adenomyosis. Issue 11 (30th July 2015) - Nakamura, Kohei; Nakayama, Kentaro; Ishikawa, Masako; Katagiri, Hiroshi; Katagiri, Atsuko; Ishibashi, Tomoka; Sato, Emi; Asakawa, Yasuyuki; Kyo, Satoru
Abstract: Aim: Conventional microwave endometrial ablation (MEA) can be insufficient to control menorrhagia resulting from adenomyosis. We compared the standard single ablation technique with multiple MEA – repeating ablation three times in the same region – in patients with adenomyosis and menorrhagia. Material and Methods: We performed single MEA in 18 patients and multiple MEA in seven patients between 2007 and 2013. We compared the efficacy of single and multiple MEA using a visual analog scale (VAS) for menorrhagia, dysmenorrhea, and patient satisfaction. We also evaluated the incidence of menorrhagia recurrence, amenorrhea, and procedure complications in relation to patients' clinical factors. Results: VAS scores for improved menorrhagia and patient satisfaction were significantly higher in the multiple MEA group than in the single MEA group; however, the operative time was longer in the multiple‐treatment group. There were no statistical differences between groups in hemoglobin levels, VAS improvement for dysmenorrhea, menorrhagia recurrence, frequency of complications, or amenorrhea rate. Conclusion: Multiple MEA successfully controls menorrhagia from adenomyosis and achieves a higher satisfaction rate than single MEA.